Solvent Recovery from Industrial Paint Waste using Batch Distillation: The Effect of Temperature - Setyawan, Mafaz; Jayanudin, J.; Maryani, Yeyen (Bumi Publikasi Nusantara, 2025)
Recovering materials from waste is a viable solution for managing paint-related organic solvent waste. This study focuses on the extraction of organic solvents from paint residues, which contain resins and pigments, to produce a renewed solvent. The method selected for recovery was distillation, which was used for optimizing the separation conditions for the solvents from their waste impurities. Using a batch distillation apparatus with a 30-L capacity, experiments were conducted at varying operating temperatures (120, 130, 140, 150, and 160°C) under a consistent vacuum pressure of 0.9 bar. The optimal results indicated that at 160°C and a vacuum pressure of 0.9 bar, a naphtha solvent with a 66.37% recovery rate was achieved at 19.91 L and an initial feed volume. This method of solvent recovery not only holds promise for waste reduction but also contributes significantly to environmental protection by minimizing pollutants.